Tree-dimensional resources: hedgerow and orchard pollen for bumble bees - Gekière, Antoine; Michel, Apolline; Semay, Irène; Tourbez, Clément; Begou, Martin; Michez, Denis; Gerbaux, Pascal; Vanderplanck, Maryse (Comptes Rendus. Chimie)
Intensive landscape modifications have led to the loss of floral resources, partly in early spring when bumble bee queens need suitable pollen to establish their brood. Adequate floral resources are also crucial to mitigate parasite infection, a stress compromising reproductive success. Among early blooming trees, willows represent an important and highly suitable pollen resource. Alas, riparian areas and their associated willows have been declining. In this study, we found that hedgerow and orchard pollen were at least as suitable as willow pollen for bumble bee survival and microcolony development. Moreover, orchard pollen seemed an interesting candidate to help reduce parasite infection, but unlikely due to its flavonoids. Such non-willow trees could then be favoured in agri-environmental schemes implemented in bee conservation strategies, but pollen chemicals underlying beneficial effects remain to be determined.